VALIDATION OF PREDICTIVE EQUATION FOR HEIGHT USING DEMI-SPAN AMONG UNIVERSITI SULTAN ZAINAL ABIDIN STAFF - HARITH, SAKINAH; JUHANIS, LUCY (International Journal of Allied Health Sciences, 2020)
Demi-span measurement is one of the alternative methods used to estimate height in the society, especially for those who cannot measure height by standing upright. This is because height is among the measures needed to determine one’s nutritional status, such as body mass index (BMI). Therefore, this study was conducted to validate the equation proposed by Ngoh et al. (2012). This cross-sectional study involved 118 employees serving at Universiti Sultan Zainal Abidin (UniSZA), Kuala Nerus, Terengganu, Malaysia, who were aged 30 to 55 years. Weight, height, and demi-span were measured using standard procedures. The results showed that the characteristics of adult anthropometrics differed by gender (p < 0.001) and age (p < 0.05). The heights calculated from the equations and the heights of the measurements had the same agreement and similarity (r = 0.944 and r = 0.949), respectively, and produced a BMI estimate that was close to the actual BMI (r = 0.997 and r = 0.996) calculated from the measured height. In conclusion, the demi-span equation showed good reliability and was suitable to estimate height and BMI among the adults in Malaysia.